2006
DOI: 10.1016/j.febslet.2006.03.045
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human d‐amino acid oxidase

Abstract: D D-Amino acid oxidase (DAAO) has been proposed to be involved in the oxidation of D D-serine, an allosteric activator of the NMDA-type glutamate receptor in the brain, and to be associated with the onset of schizophrenia. The recombinant human DAAO was expressed in Escherichia coli and was isolated as an active homodimeric flavoenzyme. It shows the properties of the dehydrogenase-oxidase class of flavoproteins, possesses a low kinetic efficiency, and follows a ternary complex (sequential) kinetic mechanism. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
272
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 131 publications
(282 citation statements)
references
References 23 publications
10
272
0
Order By: Relevance
“…Recombinant rDAAO and hDAAO were expressed in BL21(DE3)Star E. coli strain and purified as previously reported in (Frattini et al 2011) and (Molla et al 2006), respectively.…”
Section: Recombinant Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recombinant rDAAO and hDAAO were expressed in BL21(DE3)Star E. coli strain and purified as previously reported in (Frattini et al 2011) and (Molla et al 2006), respectively.…”
Section: Recombinant Proteinsmentioning
confidence: 99%
“…Thus, we first evaluated the ability of propiverine or propiverine-N-oxide to interact with recombinant rat DAAO (rDAAO). We performed spectral analyses using the recombinant rat and human (hDAAO) proteins, since it is well documented that the binding of ligands in the active site of the flavoenzyme yields to concentration-dependent perturbations of the visible absorbance spectrum (Harris et al 1999;Molla et al 2006;Frattini et al 2011). Notably, only minimal changes in the spectrum were observed following the titration with both propiverine and propiverine-N-oxide, suggesting that neither of the two compounds is an rDAAO ligand (Fig.…”
Section: Recombinant Daao Properties Are Unaffected By Propiverinementioning
confidence: 99%
See 1 more Smart Citation
“…6 We recently demonstrated that in vitro hDAAO specifically interacts with pLG72, yielding a % 200-kDa complex constituted by 2 hDAAO homodimers and 2 pLG72 monomers. [7][8][9] This interaction results in a time-dependent loss of hDAAO activity which is mainly due to alteration of the tertiary structure of hDAAO. Furthermore, we confirmed in vivo the hDAAO-pLG72 interaction and demonstrated that the cellular concentration of D-serine decreases in U87 glioblastoma cells transfected with a plasmid encoding for hDAAO but is not modified in those simultaneously transfected with cDNAs encoding both pLG72 and hDAAO.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Human DAAO shows the main properties of the dehydrogenase-oxidase class of flavoproteins and shares a low turnover number and a ternary complex (sequential) kinetic mechanism with pig kidney DAAO (pkDAAO, %85% sequence identity). 7 Indeed, this human flavoenzyme can be distinguished from the other known DAAOs because it is a stable homodimer even in the apoprotein form, because the binding of the FAD cofactor is the weakest among the known DAAOs (K d value is in the micromolar range) 1,7 and because it specifically interacts with pLG72 (which is expressed on primates only). 6 These features raise a question concerning the actual in vivo activity of hDAAO: based on the weak cofactor binding (FAD concentration in brain is estimated to be %5 lM) 14 hDAAO might be largely present in the inactive apoprotein form.…”
Section: Introductionmentioning
confidence: 99%